Application of radio-dating methods in marine areas of Greece - Pappa, F. K.; Tsabaris, C.; Patiris, D. L.; Eleftheriou, G.; Androulakaki, E. G.; Kokkoris, M.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2019)
Chronology models based on radiotracers are useful for dating aquatic sediments influenced by industrialization. Among the many natural (e.g. 7Be, 234Th,210Pb) and artificial (e.g. 137Cs,238,239,240Pu) radiotracers, the proper ones to study the industrial impact and reconstruct past events during the last 100 years, are 210Pb and 137Cs. Mining belongs to the industries with great ecological impact in the aquatic environment, as mines are situated near environmental sensitive areas such as coasts, rivers and lakes. Additionally, the accurate historical reconstruction may provide information regarding the mine footprint in the aquatic environment so as to assess the previous or the remaining contamination, in case of on-going or abandoned mines. In the present study, the retrospective investigation in a coastal area of Lavrio, near an abandoned metallic mine is attempted, using the 210Pb and 137Cs methodologies and the emerged difficulties are discussed.